Dispossession and the environment : rhetoric and inequality in Papua, New Guinea - West, Paige, 1969- (University seminars/Leonard Hastings Schoff memorial lectures., 2016)
When journalists, developers, surf tourists, and conservation NGOs cast Papua New Guineans as living in a prior nature and prior culture, they devalue their knowledge and practice, facilitating their dispossession. Paige West's searing study reveals how a range of actors produces and reinforces inequalities in today's globalized world. She shows how racist rhetorics of representation underlie all uneven patterns of development and seeks a more robust understanding of the ideological work that capital requires for constant regeneration.